THE RELATIONSHIP BETWEEN INTELLIGENCE AND GRADE POINT AVERAGE 0F MEDICAL STUDY PROGRAM STUDENTS OF MEDICAL FACULTY OF MULAWARMAN UNIVERSITY - Andi Erika Safitri; Eva Rachmi; Sulistiawati Sulistiawati (Jurnal Ilmu Kesehatan, 2019)
Abstract: A doctor is one of the professions in the health sector, in order to obtain this degree one must undergo medical education. Learning outcomes are obtained through 3P stages in the form of presage, process, and products. Presage factors, including personal and situational. Personal factors have several components including intelligence. The purpose of the study was to determine the relationship of intelligence with grade point average of the Medical Study Program of the Mulawarman University Medical Faculty. This study was an observational analytic study with cross sectional method. The data source is secondary data. The research respondents were students of the Medical Study Program of the Mulawarman University Medical Faculty who met the inclusion criteria. Analysis with chi square alternative test is Fisher's test. The results of the study found 305 respondents who met the inclusion and exclusion criteria. Overall data of male respondents were 86 people (28.2%) and female respondents there were 219 people (71.8%). The most intelligence data on respondents is the average category of 131 students (43%), the highest achievement index owned by respondents is the Good category as many as 226 students (74.1%). The overall results of the study were significance p = 0.018, seen at each grade at IV-grade (p = 0.017), III-grade (p = 0.503), II-grade (p = 1,000), I-grade (p = 0.238), can it was concluded that overall there was a correlation of intelligence with grade point average (GPA), while at each grade only at IV-grade had similar results.